Supremo Tribunal Federal e a pandemia da covid-19: a suprema corte e as suas conexões internacionais - Harigaya, Hugo Heiske (2022)
The present study aims to analyze the possible connections between the decisions handed down by the Federal Supreme Court and the guidelines from international institutions in the context of the Covid-19 pandemic.It seeks to understand how these international normative commands affect and support the sentences of the Supreme Court ministers, impacting the Brazilian legal system.The research aims to understand the Judiciary protagonism in Brazil in various political spheres and the role of the STF in international connections that provide a dialogue between the Court and the incorporation of foreign precedents. The research combines the areas of International Relations and Law, has the construction of a database related to some decisions of the Brazilian Supreme Court, composed of emblematic cases in the fight against the New Coronavirus that make use of international commands. After analyzing STF decisions in the context of the Covid-19 pandemic, concluded that the Court has made recurrent use of international commands incorporated or not by the national order, however the argumentative level of the sentences and the methodology applied demand greater advances, in in order to meet the continuous and swift evolutionary process of Brazilian society.